Determination of amino acids misincorporation in recombinant protein by mass spectrometry - Alam, MZ; Regioneiri, L; Santos, MAS (Bangladesh Journal of Animal Science, 2013)
The synthesis of protein according to genetic code of a gene determines the basis of life and a stable proteome is necessary for cell homeostatis. However, errors occur naturally during translation of protein from its mRNA, which varies from 10-3 to 10-4 per codon. These errors are more frequent in recombinant protein overexpressed in heterologous hosts and affect protein functionality. The increasing amount of nonfunctional protein is often related to mistranslation of a gene under stress. In the present study, Saccharomyces cerevisiae as a host organism to overexpress E. coli lacZ gene fusion with GST to quantify misincorporation of amino acid in GST-? galactosidase recombinant protein. The yeast was treated with various stressors such as ethanol, chromium (CrO3), and aminoglycoside antibiotic - geneticin (G418) to induce protein aggregation. The misincorporation of amino acids was studied in soluble protein fractions by mass-spectrometry to determine how much misincorporation occur. We found that under experimental stress conditions the misincorporation of amino acids ranges from 5.6 ×10-3 to 8 × 10-3, which represents 60-80 fold higher than reported level. DOI: http://dx.doi.org/10.3329/bjas.v42i1.15760 Bang. J. Anim. Sci. 2013. 42 (1): 11-19